Portuguese cinema (1960-2010) : consumption, circulation and commerce - Graça, André Rui (Tamesis, 2021)
Why has Portugal's vibrant and creative cinema industry not been more commercially successful?
Keywords: Motion picture industry -- Portugal -- History.; Motion pictures -- Portugal -- History.; Cinéma -- Industrie -- Portugal -- Histoire.; Cinéma -- Portugal -- Histoire.; Motion picture industry; Motion pictures; Portugal; History